Hypoplasia of umbilical artery - Chabes y Suárez, Álvaro (2015)
One case of hypoplasia of umbilical artery is presented in a newborn female is no evidence that birth defects up to 2 years old. It emphasizes the need to study this type of pathology, when early, can give flattering surgical outcomes in terms of correcting the defects present.